2013
DOI: 10.2146/ajhp110654
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of preparation of i.v. medication syringes for anesthesiology

Abstract: Analysis of different i.v. formulations of four medications prepared in syringes by anesthesiologists revealed a high rate of discrepancies between ordered and actual drug concentrations, suggesting a need for increased institutional efforts to prevent errors during the preparation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 8 publications
1
18
1
Order By: Relevance
“…Analyses of the content of unused syringes containing drugs regularly used in anaesthesiology (fentanyl, thiopental, lidocaine, atracurium) revealed that 29% showed drug concentrations outside the specified acceptability range and 4% contained more than twice the targeted drug concentration. Errors closely correlated with multiple dilutions of high-strength formulations, and hence measurements of small volumes of initial drug solution, and these were seen particularly in preparations involving fentanyl 41. The complexity of preparation, often involving multiple calculations, was implicated in dilution error.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of the content of unused syringes containing drugs regularly used in anaesthesiology (fentanyl, thiopental, lidocaine, atracurium) revealed that 29% showed drug concentrations outside the specified acceptability range and 4% contained more than twice the targeted drug concentration. Errors closely correlated with multiple dilutions of high-strength formulations, and hence measurements of small volumes of initial drug solution, and these were seen particularly in preparations involving fentanyl 41. The complexity of preparation, often involving multiple calculations, was implicated in dilution error.…”
Section: Resultsmentioning
confidence: 99%
“…A number of publications suggest that a high incidence of imprecision and dilution errors occur in the preparation of intravenous medicines and the preparation of small volumes of medicines is inaccurate 13 26 41 56…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration measurements conducted on these syringes found similar results: the differences between expected and measured concentrations were greater than 50% in 8% of the cases, and greater than 100% in 4% of the cases. 8 The incidence of discrepancies was highest in the paediatric operating room. The measures adopted to improve practice involved changes in syringe labelling with the use of specific colours, and of new standards in drug labelling with recording of weight, volume and concentration and lastly with the introduction of prefilled syringes to remove the risk of dilution error altogether.…”
Section: Safety In Perspectivementioning
confidence: 99%
“…preparations for anesthesiology and chemotherapy has been reported to involve higher rates of discrepancy from designated ranges of acceptability. 3,7 A study that assessed the accuracy of volumetric technique in the preparation of chemotherapy doses found that 71.7% of the doses prepared were within ±5% and 87.4% were within ±10% of the ordered dose. 8 The study authors suggested that "the process of volumetric technique alone is not sufficient to accurately prepare chemotherapy doses, and a focus of improving the process of preparing i.v.…”
mentioning
confidence: 99%